REPUTASI AUDITOR SEBAGAI PEMODERASI PENGARUH AUDIT FEE PADA AUDITOR SWITCHING - Indah Sari, Ika Wulan; Widanaputra, A.A. G.P (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of audit fee to the auditor switching. In addition , this study also aimed to determine the effect on the auditor's audit fee switching to the auditor 's reputation as a moderating . This study was conducted on 145 manufacturing companies listed on the Stock Exchange in 2010-2014 . The results of this study indicate that the audit fee positive effect on the auditor switching. This shows that the higher audit fee offered auditor , the company will be more frequent switching auditors . Additionally auditor reputation weaken the influence of audit fees on auditor switching. This means companies that have used the services of a reputable accounting firm will not perform switching auditors audit fee despite being offered KAP relatively high repute .
Keywords: audit fee, reputasi auditor, auditor switching